ANALISIS PENERIMAAN RETRIBUSI PARKIR DI TEPI JALAN UMUM TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA CIREBON TAHUN 2019-2023 PERSPEKTIF EKONOMI ISLAM - Putri, Diva Kartika Wahyudin; Sukardi, Didi; Busthomi, Achmad Otong (FEB Universitas Sultan Ageng Tirtayasa, 2025)
This research analyzes the growth, effectiveness and contribution of parking fees to PAD based on an Islamic economic perspective, using mixed methods with a descriptive approach. The research results show that the growth of parking fees on PAD with an average of 8.22% is said to be less successful. The effectiveness of parking levies on PAD is not effective, with an average of 51.2%. The contribution of parking fees to PAD is very less, with an average of 0.44%. In an Islamic perspective, the management of fees fulfills the terms and conditions of the contract, but is considered fasid because there are elements of tadlis and gharar in collecting parking fees. The principles of monotheism, morals, balance and justice have been implemented, but non-compliance with tariffs is still an obstacle. The implementation of maqashid sharia regarding the protection of religion, life, lineage and property has been implemented, but transparency and management efficiency need to be improved.